Visual Basic .NET for experienced programmers. - Deitel, Harvey M., 1945-; Deitel, Paul J., 1969-; Nieto, T. R., ....- (Upper Saddle River : Prentice Hall, 2003)
"The experienced programmer's Deitel Live-Code guide to Visual Basic .NET and the powerful Microsoft .NET Framework. Written for programmers with backgrounds in C++, Visual Basic, Java or other high level languages, this book applies the Deitel signature Live-Code approach to teaching programming and explores Microsoft's Visual Basic .NET language in depth. Visual Basic .NET concepts are presented in the context of fully tested programs, complete with syntax highlighting, detailed line-by-line descriptions and program outputs. The book features 192 Live-Code programs that contain 20,337 lines of proven Visual Basic .NET program code. In addition, the book includes 319 programming tips that help you build applications that are portable, reusable and optimized for performance." Start with condensed discussions of the Visual Studio .NET IDE, control structures, procedures and arrays. Then move rapidly to more advanced topics, including Windows Forms, ADO .NET, ASP .NET, ASP öNET Web services, network programming and XML processing. Along the way you will enjoy the Deitels' classic treatment of object-based and object-oriented programming. When you are finished, you will have everything you need to build next-generation Windows applications, Web applications and XML Web services.
Keywords: Visual basic (programmeertaal).